Optimization of preventative maintenance strategies for bridges - Tantele, Elia; Onoufriou, Toula; Mulheron, Mike J. (My University, 2006)
The use of preventative maintenance (PM) has been acknowledged as an effective way of reducing the whole life cost of maintaining bridges in good, safe and functional condition. However, there are many uncertainties associated with the need and effectiveness of PM. Such uncertainties if not addressed can lead to incorrect decisions and wastage of resources. In addition optimization procedures are necessary to produce strategies with minimum cost while maintaining the reliability of the bridge at an acceptable level. This paper examines the issue of effectiveness of different PM on reinforced concrete bridges deteriorating due to the corrosion of reinforcement from chloride ions. It investigates the applicability of an optimization methodology, using the principles of genetic algorithm (GA) to identify optimum PM strategies based on their effectiveness and cost.
Keywords: Building materials; Reinforced concrete; Concrete bridges